Frugal Living is A New Alternative Gen Z Lifestyle - Rahmasari, Himas Arum Syarifah; Mafruhah, Izza; Istiqomah, Nurul; Gravitiani, Evi (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This research novelty is about the location of Surakarta City and the relationship between lifestyle and love of money towards frugal living. Research Objectives: This study examines the frugal living practices of Generation Z in Surakarta City. Research Methods: This study used quantitative methods with PLS-SEM for analysis. The variables in this study include frugal living, lifestyle, love of money, and financial management. Empirical Results: The findings show that lifestyle and love of money significantly influence frugal living among Generation Z in Surakarta City. At the same time, financial management does not have a significant impact on frugal living among Generation Z in Surakarta City. Implications: These results highlight the importance of financial literacy improvement policies that include environmentally friendly consumption patterns and raise awareness among Generation Z to use local products. JEL Classification: D14, D91, G41 How to Cite:Rahmasari, H. A. S., Mafruhah, I., Istiqomah, N., & Gravitiani, E. (2025). Frugal Living is A New Alternative Gen Z Lifestyle. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 423-436. https://doi.org/10.15408/sjie.v14i2.46418.